The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acsami.9b11119
|View full text |Cite
|
Sign up to set email alerts
|

Electronic States and Transport Phenomena of Pt Nanoparticle Catalysts Supported on Nb-Doped SnO2 for Polymer Electrolyte Fuel Cells

Abstract: Semiconducting oxide nanoparticles are strongly influenced by surface-adsorbed molecules and tend to generate an insulating depletion layer. The interface between a noble metal and a semiconducting oxide constructs a Schottky barrier, interrupting the electron transport. In the case of a Pt catalyst supported on the semiconducting oxide Nb-doped SnO2 with a fused-aggregate network structure (Pt/Nb-SnO2) for polymer electrolyte fuel cells, the electronic conductivity increased abruptly with increasing Pt loadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 50 publications
4
27
0
Order By: Relevance
“…Kakinuma et al. [ 402 ] reported that the Pt deposited onto Nb‐doped SnO 2 formed a PtSn alloy between the catalyst and the surface, which enhanced the electron transfer to the catalyst by reducing the Schottky‐type barrier. They also reported that the conductivity had a significant dependence on the Pt loading.…”
Section: Catalyst Layer Structurementioning
confidence: 99%
“…Kakinuma et al. [ 402 ] reported that the Pt deposited onto Nb‐doped SnO 2 formed a PtSn alloy between the catalyst and the surface, which enhanced the electron transfer to the catalyst by reducing the Schottky‐type barrier. They also reported that the conductivity had a significant dependence on the Pt loading.…”
Section: Catalyst Layer Structurementioning
confidence: 99%
“…We reported that the PtSn alloy was inserted in the heterointerface between Pt and SnO 2 , and then, the Pt catalyst became well-orientated along with the relaxation of the lattice distortion and formation of the intermediate phase of PtSn alloy. The latter would diminish the effect of a possible Schottky barrier, enhance the high electronic conductivity, and impede the movement of Pt catalyst particles, as reported in previous papers. , The loading amounts of Pt 100– x Co x alloy were 15.4 wt % ( x = 19), 16.4 wt % ( x = 23), 18.6 wt % ( x = 24-HR), 17.4 wt % ( x = 25), and 17.9 wt % ( x = 33). The chemical composition ratios (Pt/Co) of all of the catalysts also corresponded well to the chemical ratios measured by ICP-MS.…”
Section: Resultsmentioning
confidence: 61%
“…The Pt 75 Co 25 alloy was also well-oriented with respect to the Ta–SnO 2 support (inset of Figure ). In our previous paper, we evaluated the interface between the Pt catalyst and the SnO 2 support by XPS, hard X-ray photoelectron spectroscopy (HAXPES), and STEM–EDX and confirmed that the PtSn metal alloy layer was inserted at the interface . The PtSn metal alloy was formed during the heat treatment procedure after the Pt catalyst was deposited on the SnO 2 support.…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…From these observations, a pronounced core–shell structure with an Er-rich shell is indicated for sample A, whereas in sample B, intermixing between Y, Yb, and Er with a slight enrichment of Yb in the near-surface region is consistent with the data. Such spatial distribution of the sensitizer and activator ions enables control of the donor–acceptor interaction and dynamics thereby eliminating or reducing deleterious cross-relaxation between lanthanide dopants and thus fine tuning of the optical properties [ 68 , 69 ]. Additionally, the location of emitting Er 3+ centres in the shell region enables very efficient luminescence resonance energy transfer (LRET) to organic molecules bound to the surface of the UCNPs due to the minimum distance between LRET donors and acceptors.…”
Section: The Ideal Case—a First Look On Oleic Acid Stabilized Yber-do...mentioning
confidence: 99%